The Language of Propaganda in Governance: The Nigerian Situation - Ifeoma Nwosu-Okoli; Ngozi Anyachonkeya (European Scientific Journal, ESJ, 2023)
Language is a unique gift to humanity by the Omniscient God. By means of language, we build or end a relationship, forge alliance, build bridges of unity and cooperation among peoples and groups. By means of language, also, we find a viable instrument to achieve participation and exclusion in political and diplomatic maneuvering. Formal or informal discourse may be achieved through vocal utterance, written medium or even paralinguistic features. Language, in effect, plays inestimable role in all aspects of life. This paper, in a special way, examines the impact of language in governance. Since English is Nigeria’s official language, the essay has, by purposeful random sampling, chosen the meta language of English, of all the myriads of languages spoken in Nigeria, to engage our discourse and to ascertain the impact of language in governance. Again, since charity, they say, begins at home (but should not end there), the essay has chosen Nigeria to query the impact of the English language in (political) governance. The paper upholds the platitude which holds that much is expected from the one to whom much is given. In view of this, the study asserts that political governance in Nigeria is hard work for the fact that Nigeria is a conglomerate of peoples, national groups and tongues yoked together by the Lugardian amalgamation of January 1, 1914. The salient index that wields the fragile nation state together is diversity, amidst mutual suspicion among the diverse ethnic groups. The essay uses literary or library research to probe into the recesses of language and language theories for recommending to the political leaders in governance how they should manage language so that our beloved nation is not set ablaze as a result of language mismanagement.